Primary care perspectives on pandemic politics. Issue 8 (2nd September 2021) - Goodyear-Smith, Felicity; Kinder, Karen; Eden, Aimee R.; Strydom, Stefan; Bazemore, Andrew; Phillips, Robert; Taylor, Melina; George, Joe; Mannie, Cristina
ABSTRACT: While the COVID-19 pandemic now affects the entire world, countries have had diverse responses. Some responded faster than others, with considerable variations in strategy. After securing border control, primary health care approaches (public health and primary care) attempt to mitigate spread through public education to reduce person-to-person contact (hygiene and physical distancing measures, lockdown procedures), triaging of cases by severity, COVID-19 testing, and contact-tracing. An international survey of primary care experts' perspectives about their country's national responseswas conducted April to early May 2020. This mixed method paper reports on whether they perceived that their country's decision-making and pandemic response was primarily driven by medical facts, economic models, or political ideals; initially intended to develop herd immunity or flatten the curve, and the level of decision-making authority (federal, state, regional). Correlations with country-level death rates and implications of political forces and processes in shaping a country's pandemic response are presented and discussed, informed by our data and by the literature. The intersection of political decision-making, public health/primary care policies and economic strategies is analysed to explore implications of COVID-19's impact on countries with different levels of social and economic development.